Many buddhas, one Buddha: a study and translation of Avadānaśataka 1-40 - Appleton, Naomi (Equinox, 2020)
Crossing the flood of rebirth -- The Avadānaśataka -- Many buddhas -- Śākyamuni's past lives -- Independent buddhahood -- Miracles, offerings, aspirations and predictions -- And then the Buddha smiled -- Structure of the Avadānaśataka -- Many buddhas, many Buddhisms -- One Buddha, many lessons -- First decade (stories 1-10) -- Second decade (stories 11-20) -- Third decade (stories 21-30) -- Fourth decade (stories 31-40)